Crescent and electoral strength: Islamic party portrait of reform era in Indonesia - Romli, Lili (Universiti Kebangsaan Malaysia, 2013)
The establishment of Islamic political parties in the reform era in Indonesia after the fall of Suharto (1998), considered as resurgence of political stream. There are several factors that led to the revival of Islamic parties after the New Order, the theological factor, historical, sociological, and reform factor. The presence of Islamic political parties after the New Order was apparently diverse and fragmented. In the political elite of Islam itself in establishing a political party based on Islam and there is also based on nationality, and in establishing political party was using substantially approach and there is also that use formalistic approach. In the reform era elections, political Islam has failed, in which Islamic parties do not receive optimal support from voters Islam. The failure of Islamic parties in election of reform era is caused of factor among Muslims has been change the orientation of political views. Islamic parties in the reform era stuck in a political myth quantity, and Islamic parties are also fragmented and fractured in to small forces.